Physics-guided neural networks with Monte Carlo dropout for full-probabilistic durability design of concrete exposed to marine environments - Weiyang Wang; Yujie Lu; Qingfang Lv; Yu Zhang (Ocean Engineering, 2026)

Interaction mechanism between infill walls and prestressed self-centering frames - Yujie Lu; Juewen Wang; Qingfang Lv; Ye Liu; Jun Xu; Huanlong Ding (Engineering Structures, 2026)

Carbon sphere template derived TiO2 hollow sphere with nitrogen doping and carbon sensitization for visible-light driven cyclohexane oxidation and tetracycline hydrochloride degradation - Guang Xu; Ying Zhang; Changyou Lu; Dongxuan Guo; Lina Liu; Qingfang Deng; Shangkun Ma; Xin Wang (Journal of Water Process Engineering, 2025)

Experimental and theoretical study on the eccentric compressive behavior of tie-reinforced CFNRST columns - Xinlei Lv; Qingfang Lv; Yang Qian; Yujie Lu (Engineering Structures, 2025)

Novel oleanolic acid derivatives containing piperazine pyrimidine moieties: design, synthesis, and antimicrobial activity - Fengwei Ma; Qingfang Deng; Yihao Lu; Zhenghong Jia; Su Xu; Qiang Fei; Haijiang Chen; Wenneng Wu (Molecular Diversity, 2025)

β,β-Dimethylacrylshikonin Alleviates Zebrafish (Danio rerio) Soyasaponin-Induced Enteritis by Maintaining Intestinal Homeostasis and Improving Intestinal Immunity and Metabolism - Ming Liu; Xin Lu; Leong-Seng Lim; Yinhui Peng; Lulu Liu; Kianann Tan; Peng Xu; Mingzhong Liang; Yingrui Wu; Qingfang Gong; Xiaohui Cai (Fishes, 2025)
Soyasaponin intolerance is common in ancient fish species, making them susceptible to enteritis caused by dietary soybean meal. β,β-Dimethylacrylshikonin is the key active monomer found in Lithospermum erythrorhizon and is known for its multiple pharmacological activities. However, its effect on soybean meal-induced enteritis remains unknown. The administration of 2 g/kg of β,β-Dimethylacrylshikonin (LE) effectively alleviated 5 g/kg of soyasaponin-induced histopathological changes and dysfunction, as evidenced by the expression of inflammation-related genes (il-1β, il-8, and il10). Regarding the gut microbiota composition, LE therapy decreased the population of inflammation-linked Proteobacteria and concurrently elevated the proportion of Fusobacteriota, effectively sustaining the balance of the zebrafish gut microbiota. Moreover, at the genus level, LE treatment also increased the abundance of Cetobacterium. Transcriptional results suggested that LE intervention mainly regulated immune-related pathways, including cytokine–cytokine receptor interaction, the TGF-beta signaling pathway, taurine and hypotaurine metabolism, and arachidonic acid metabolism. In conclusion, 5 g/kg of soyasaponins caused intestinal injury in zebrafish, and β,β-Dimethylacrylshikonin can reduce intestinal inflammation by regulating the intestinal microbial balance and metabolic disorder, with the best effect at 2 g/kg.

High-temperature pressure cooking on the quality of Basa (Pangasius bocourti) fish maw: Gelling, in vitro digestion and proteomic analysis - Shiyu Wu; Qiuyu Lu; Lianying Xu; Shengnan Zhan; Wenge Yang; Qingfang Ying; Haixia Yu; Ying Liu; Tao Huang (Food Chemistry, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

Effects of Sophora flavescens ethanol extract supplementation in high soybean meal diets on growth, intestinal antioxidant status and immune response in Pearl Gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Xin Lu; Yinhui Peng; Kianann Tan; Bingxiang Zhou; Qingfang Gong; Peng Xu; Xueying Liang; Wenjie Liu; Kit Yue Kwan; Yingrui Wu; Xiaohui Cai (Aquaculture International, 2025)

Transcriptome analysis of human spermatozoa with different DNA fragmentation index using RNA sequencing - Kailin Yang; Xue Sun; Qiyuan Zheng; Chen Pan; Siyuan Wang; Qingfang Lu; Changlong Xu; Yangqing Lu (Reproductive Biology, 2024)

Effects of Sophora flavescens dietary supplementation on the growth performance, haematological indices, and intestinal bacterial community of Oreochromis niloticus - Xin Lu; Yingrui Wu; Yinhui Peng; Wenjie Liu; Ming Liu; Peng Xu; Kianann Tan; Xueying Liang; Xiaohui Cai; Qingfang Gong (Journal of Fish Biology, 2024)
Sophora flavescens is considered to be of various medicinal and economic importance. Previous studies have shown that it has antibacterial, antioxidant, and immune‐enhancing functions. To explore the full potential of S. flavescens in fish feed development, we investigated the effects of different levels of S. flavescens added to the diet on the growth performance, haematological indices, and the intestinal bacterial community of Nile tilapia ( Oreochromis niloticus ). The feeding trial lasted for 56 days, and the initial weight of the fish was 40.00 ± 5.00 g. Nile tilapia were randomly divided into six groups: a control group (CN) and five S. flavescens supplementation groups (0.02%, 0.04%, 0.08%, 0.16%, and 0.3% [w/w] of S. flavescens in diet). The growth performance of fish increased first and then decreased with the increase of S. flavescens supplemental level. Compared with other experimental groups, the growth performance of fish supplemented with 0.08% S. flavescens was significantly improved ( p S. flavescens , reaching the highest level at 0.08% ( p S. flavescens and reached the lowest value at 0.08% ( p S. flavescens was 0.04% in each treatment group ( p Bacteroides dominated the gut communities, and compared with the control group, two uncultured bacteria were suppressed. In addition, when the supplemental level of S. flavescens was more significant than 0.04%, the proliferation of Arcobacter cryaerophilus , Solibacillus silvestris , and Escherichia sp. in the gut of Nile tilapia was promoted. The results revealed that S. flavescens , as an additive to the Nile tilapia diet with levels ranging from 0.04% to 0.08%, can enhance the growth performance and immunity and promote the proliferation of intestinal beneficial bacteria of Nile tilapia.

Hysteresis performance and damage mode of self-centering frame with masonry infill wall: Experimental study assisted with DIC technique - Yujie Lu; Qingfang Lv; Ye Liu (Engineering Structures, 2024)

Experimental study on the hysteretic performance of a self-centering frame infilled with a bamboo wall - Yujie Lu; Ye Liu; Qingfang Lv (Engineering Structures, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Experimental evaluation of fracture toughness of bamboo fiber reinforced high performance lightweight aggregate concrete - Jing Shi; Yujie Lu; Ran Zhu; Ye Liu; Yu Zhang; Qingfang Lv (Engineering Structures, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Efficacy of using thromboelastography to detect coagulation function and platelet function in patients with acute cerebral infarction - Qingfang Yuan; Lu Yu; Feng Wang (Acta Neurologica Belgica, 2021)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Enhanced amplification of bacterial and fungal DNA using a new type of DNA polymerase - Qingfang Lu; Hanqiao Hu; Junjie Mo; Liangzhu Shu (Australasian Plant Pathology, 2012)